Analisis Pengungkapan Corporate Social Responsibility (CSR) Berbasis Islamic Social Reporting (ISR) Pada Bank Syariah Mandiri Periode 2014-2016 - Mutia Rahmawati Isya (Iqtishodia: Jurnal Ekonomi Syariah, 2019)
This study aims to describe the intensity of Islamic Social Reporting (ISR) -based Corporate Social Responsibility (CSR) disclosure at Bank Syariah Mandiri. This research uses a qualitative approach. The object of this research is Bank Syariah Mandiri. Data analysis uses Content analysis. The period used in this study was limited to 2014-2016 in the annual report of Bank Syariah Mandiri. The results showed that the calculation of the ISR index on BSM from 2014-2016 showed that the overall intensity of BSM's social responsibility disclosure was informative. Although the cumulative intensity of BSM social responsibility disclosure is informative, on each ISR index shows different results, and of 6 (six) disclosure themes only the theme of corporate governance shows the highest value of the BSM ISR index in 2014-2016 of 100%.